THE EFFECT OF AUDIT MARKET COMPETITION ON EARNINGS MANAGEMENT WITH AUDITOR INDUSTRY SPECIALIZATION AS A MODERATING VARIABLE - Triani Putri, Irfi Ade; Zaki Fakhroni (Media Riset Akuntansi, Auditing & Informasi, 2024)
This study aims to analyze the effect of audit market competition on earnings management, by considering auditor industry specialization as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022. To test this relationship, this study uses financial statement data from 75 manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sample of this study was selected using purposive sampling method. Data analysis was performed using the IBM SPSS 25 analysis tool and using moderated regression analysis to test the hypothesis. The results showed that competition in the audit market has a negative and significant effect on earnings management. This indicates that the higher the level of competition in the audit market, the lower the occurrence of earnings management. This study also found that auditor industry specialization has a significant positive effect in moderating the relationship between audit market competition and earnings management.